2019
DOI: 10.3390/medicines6030084
|View full text |Cite
|
Sign up to set email alerts
|

Pruritus Associated with Commonly Prescribed Medications in a Tertiary Care Center

Abstract: Background: Sparse data are available on rates of drug-induced pruritus, a well-recognized adverse reaction. We sought to assess relative rates of pruritus associated with commonly prescribed medications. Methods: Using the electronic medical record system EPIC, retrospective data were collected on patients seen at Johns Hopkins who received a medication of interest in a five-year period (2013–2018). Sequential criteria were used to identify the subpopulation who presented with a chief complaint of “pruritus” … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Also, Benson et al declared that opioid-induced pruritus (OIP) is one of the most common adverse effects of oral and neuraxial opioids (12). Huang et al's study on relative rates of pruritus associated with common drugs in adults showed that among all drugs investigated, heparin (1.11%), trimethoprim-sulfamethoxazole (1.06%), and calcium channel blockers (0.92%) were associated with the highest rates of pruritus, their study was conducted on adult and in chronic drug users (13). Szarvas et al reported the induction of OPI after intrathecal and epidural opioids varies between 30 and 100% ( 14).…”
Section: Discussionmentioning
confidence: 99%
“…Also, Benson et al declared that opioid-induced pruritus (OIP) is one of the most common adverse effects of oral and neuraxial opioids (12). Huang et al's study on relative rates of pruritus associated with common drugs in adults showed that among all drugs investigated, heparin (1.11%), trimethoprim-sulfamethoxazole (1.06%), and calcium channel blockers (0.92%) were associated with the highest rates of pruritus, their study was conducted on adult and in chronic drug users (13). Szarvas et al reported the induction of OPI after intrathecal and epidural opioids varies between 30 and 100% ( 14).…”
Section: Discussionmentioning
confidence: 99%
“…These adverse reactions can be chronic or acute and the pruritus generated can occur via direct skin inflammation or through systemic mediators depending on the causative drug [15]. In addition to the significant impact on quality of life pruritus can have, drug-induced pruritus also makes patients less compliant to their medication regimens [16]. Huang et al performed a study to assess the rates of pruritus associated with commonly prescribed medications [16].…”
Section: Epidemiologymentioning
confidence: 99%
“…In addition to the significant impact on quality of life pruritus can have, drug-induced pruritus also makes patients less compliant to their medication regimens [16]. Huang et al performed a study to assess the rates of pruritus associated with commonly prescribed medications [16]. Using retrospective data of 9802 patients with pruritus after drug initiation, they found the highest rates of pruritus in patients taking heparin, trimethoprim-sulfamethoxazole, and calcium channel blockers [16].…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…A pulse oximeter design based on Raspberry [12], pulse oximeter [13], heartbeat monitoring [14], IoT device for heart problem detection [15] and Temperature-Humidity measurement system [16] has already been acknowledged in our work. We thought of using a unique robotics utilization and prescribed medicine care [17] for the healthcare digitalization sector [18]. In the controlling portion, some research based on path-finding autonomous movement [19], obstacle avoidance [20], [21], some are based on android app related user-end manual controlling [22].…”
mentioning
confidence: 99%